Improving Interpersonal Communication Quality of Students Through Social Guidance: Evaluation of Effectiveness and Implications - Rizal, Syamsul (Jurnal Inovasi Pengabdian Masyarakat Pendidikan, 2023)
Social guidance is guidance given to individuals to get to know their environment so that they can socialize well and become responsible individuals which is carried out at SMP N 2 Rejang Lebong. The social problems that are often faced by students within the scope of school are related to relationships between individuals or relationships between individuals and the social environment such as difficulty in making friends, alienation from group work, and others. Research to know the interpersonal communication of students at school. This type of research is quantitative. The population in this study was students of SMP Negeri 01 and the sample population of class VII A amounted to 30 people and the sample used sampling techniques. Data collection is observation, interviews, and questionnaires. The data analysis technique with product moment correlation statistics. The results of the study The relationship between the effectiveness of student social guidance in interpersonal communication at SMP N 2 Rejang Lebong in grade VII is mostly 29.06% which is included in the influential category, which means that there is a significant influence between peers. The way of interpersonal communication between grade VIII students at SMP N 2 Rejang Lebong is mostly 37.20% who fall into the high category. High here means that most teenagers or students can already communicate with their peers.